Aspirin and Risk of Subarachnoid Hemorrhage: Systematic Review and Meta-Analysis. Issue 5 (May 2017) - Phan, Kevin; Moore, Justin M.; Griessenauer, Christoph J.; Ogilvy, Christopher S.; Thomas, Ajith J.
Abstract : Background and Purpose—: Recent studies have suggested that the use of low-dose aspirin may reduce the risk of aneurysmal subarachnoid hemorrhage (aSAH). We aimed to evaluate any association between aspirin use and risk of aSAH based on the literature, and whether this is influenced by duration or frequency of aspirin use. Methods—: A search of electronic databases was done from inception to September 2016. For each study, data on risk of aSAH in aspirin versus nonaspirin users were used to generate odds ratios and 95% confidence intervals, and combined using inverse variance–weighted averages of logarithmic odds ratios in a random-effects models. Results—: From 7 included studies, no significant difference was noted between aspirin use of any duration or frequency and nonaspirin users (odds ratio, 1.00; 95% confidence interval, 0.81–1.24; P =0.99). We found a significant association between short-term use of aspirin (<3 months) and the risk of aSAH (odds ratio, 1.61; 95% confidence interval, 1.20–2.18; P =0.002). No significant difference was found in terms of risk of aSAH for 3 to 12 months, 1 to 3 years, and >3 years of durations of use. No significant association was found between infrequent aspirin use (⩽2× per week) or frequent use (≥3× per week) with risk of aSAH. Conclusions—: Current evidence suggests that short-term (<3 months) use of aspirin is associated with increased risk of aSAH. Limitations include substantial heterogenity of the included studies. The role of long-term aspirin in reducing risk of aSAH remains unclear and ideally should be addressed by an appropriately designed randomized controlled trial. Abstract : Supplemental Digital Content is available in the text.